Carbon nanotube fiber-based high-performance force and position sensors for smart fabrics and the Internet of things - Jeon, Dae-Young; Park, Jimin; Lee, Changwoo; Kim, Seung Min (American Institute of Physics Publising LLC, 2023)
Carbon nanotube (CNT) fibers are used in various applications, such as electrical cables, supercapacitors, physical sensors, artificial muscles, and electronic devices, due to their excellent mechanical, thermal, and electrical properties. Herein, the orientation-dependent electrical characteristics of a CNT fiber array were investigated. A force resistive sensor with good sensitivity and reliable operation was developed using the array and integrated with a real-time data storage and wireless monitoring system. In addition, a CNT fiber-based position sensor was developed for application in smart fabrics. This study introduces an easy-to-manufacture, low-cost, robust CNT fiber-based sensing platform that can be used with an open-source microcontroller for integration with the Internet of things.